Analisis Interface Bimetal Aluminium-Tembaga yang Dibuat dengan Pengecoran Sentrifugal Variasi Kecepatan Putar - Nugroho Santoso; Bambang Suharnadi (Jurnal Engine: Energi, Manufaktur, dan Material, 2020)
Bimetallic is a combination of two metals that forms a metallurgical bond. Bimetallic made by centrifugal casting has not been developed much, so there is no recommendation for optimum mould rotational speed to produce products as needed. The research was conducted to determine the rotation of the mould in centrifugal casting, resulting in a unified interface with a strong metallurgical bond. The materials used for the manufacture of bimetallic are aluminum and copper. Aluminum is melted at a temperature of 700ºC, while copper is melted at a temperature of 1,150ºC. The metallic liquid was poured on a rotating mould with a filling speed of 0.20 kg/s. The variations in the rotational speed of the mould when pouring are 350, 400, and 450 rpm. The pouring of metal liquids is carried out alternately. First, aluminum is poured into the mould. Then after the aluminum temperature has dropped to 350ºC, copper is poured into the mould to form aluminum-copper bimetallic in the form of a bushing. The results showed that the width of the interface increases with the increased rotation of the mould during the pouring process. The hardness and wear resistance of interfaces are increased compared to base metals in aluminum and copper. The increase in hardness and wear resistance is due to the formation of AlCu, Al2Cu and Al4Cu9 compounds in the interface area.Bimetal adalah gabungan dua logam yang membentuk ikatan metalurgi. Bimetal yang dibuat dengan pengecoran sentrifugal belum banyak dikembangkan, sehingga belum ada rekomendasi kecepatan putar cetakan yang optimum untuk menghasilkan produk sesuai kebutuhan. Penelitian dilakukan untuk menentukan putaran cetakan pada pengecoran sentrifugal, sehingga dihasilkan penyatuan interface dengan ikatan metalurgi yang kuat. Bahan yang digunakan untuk pembuatan bimetal adalah aluminium dan tembaga. Aluminium dicairkan pada temperatur 700ºC, sedangkan tembaga dicairkan pada temperatur 1.150ºC. Cairan logam dituang pada cetakan yang berputar dengan kecepatan pengisian 0,20 kg/s. Variasi kecepatan putaran cetakan saat penuangan adalah 350, 400, dan 450 rpm. Penuangan cairan logam dilakukan secara bergantian. Pertama aluminium dituang pada cetakan, kemudian setelah temperatur aluminium turun hingga 350ºC, tembaga dituang ke dalam cetakan sehingga terbentuk bimetal aluminium-tembaga yang berbentuk bushing. Hasil penelitian menunjukkan bahwa lebar interface meningkat seiring peningkatan putaran cetakan saat proses penuangan. Kekerasan dan ketahanan aus interface meningkat dibanding logam dasar aluminium dan tembaga. Peningkatan kekerasan dan ketahanan aus disebabkan terbentuknya senyawa AlCu, Al2Cu dan Al4Cu9 pada daerah interface.